HUBUNGAN STATUS GIZI DENGAN USIA MENARCHE PADA REMAJA PUTRI - Esti Rahayu; Hikmatul Khoiriyah (Jurnal Kesehatan, 2023)
According to the World Health Organization (WHO) the age range for menarche in adolescents is between the ages of 10-19 years. The results of the 2018 Riskesdas show that the average age of menarche in Indonesia is 13 years, with an earlier occurrence at the age of less than 9 years or later until the age of 17. The research method used was cross sectional. This research was conducted at SMPN 3 Batanghari Nuban with a total sample of 63 respondents. The results obtained from the 63 respondents studied were 50 respondents with good nutrition and abnormal menarche age, 48 respondents in the age category <12 years and > 14 years. In this study, it was found that the age of menarche was highest in the age group <12 years. In addition, many adolescents with good nutritional status had menarche <12 years. Relationship between nutritional status and menarche age. Factors that affect the age of menarche are not only nutritional status but there are several other factors including environment, socio-economic, exposure to visual videos and others. It is hoped that more in-depth research will be carried out on other factors that influence the age of menarche. Keywords : Menarche, Teenager, Age At Menarche, Nutritional Status